1993
DOI: 10.1111/j.1365-2249.1993.tb07957.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of IL-8 in patients with HIV infection

Abstract: SUMMARYScrum levels oflI.-8 were determined in HlV-infected individuals and the results were compared with those for HIV controls. The IL-8 levels were measured by an ELISA wilh a MoAband a polyelonal antibody to recombinant IL-8. The means and 95"!, confidence intervals of lL-8 in sem of 36 HIVinfected individuals and 32 matched controls were 275 and 216 .349 pg/ml, and 8 and 4 14 pg/ml. respeelively. showing a 34-fold increase in IL-8 in the eirculation of HlV-infected individuals. This increase does not app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 16 publications
1
31
0
1
Order By: Relevance
“…Several studies have shown the involvement of IL-8 in HIV-1 replication and AIDS pathogenesis, revealing that: (1) IL-8 secretion is enhanced in the serum, plasma, CNS, and lymphoid tissue of HIV-1 patients [44][45][46][47] ; (2) IL-8 is induced by HIV-1 infection 48 and by HIV-1 proteins 49 ; (3) IL-8 stimulates HIV-1 replication and spread 42,46 ; and (4) levels of IL-8 are increased in the brains of HIV-1 patients suffering with HIV-1-associated dementia, and this chemokine synergistically enhances MCP-1-mediated monocyte migration. 49 At present, the p17 protein is the target of a therapeutic vaccine aimed at boosting and better directing the immune response against For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the involvement of IL-8 in HIV-1 replication and AIDS pathogenesis, revealing that: (1) IL-8 secretion is enhanced in the serum, plasma, CNS, and lymphoid tissue of HIV-1 patients [44][45][46][47] ; (2) IL-8 is induced by HIV-1 infection 48 and by HIV-1 proteins 49 ; (3) IL-8 stimulates HIV-1 replication and spread 42,46 ; and (4) levels of IL-8 are increased in the brains of HIV-1 patients suffering with HIV-1-associated dementia, and this chemokine synergistically enhances MCP-1-mediated monocyte migration. 49 At present, the p17 protein is the target of a therapeutic vaccine aimed at boosting and better directing the immune response against For personal use only.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 contain a STAT binding element in its promoter region, and inflammation and oxidative stress induce IL-6 expression in macrophages (Lee et al, 2006). Human clinical and autopsy studies suggest that viral-induced inflammation and dysregulation of cytokine expression play a major role in the pathogenesis of HIV-1 infection and disease progression (Breen et al, 1990; Kedzierska and Crowe, 2001; Matsumoto et al, 1993). HIV-1 gp120-induced dysregulation of cytokine expression was also demonstrated in laboratory and animal models studies, and gp120 upregulated IL-6 and IL-8 expression in mononuclear phagocytes and glial cells (Capobianchi et al, 1997; Oyaizu et al, 1991; Yeung et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…HIV-1 infection alters cytokine secretion both in vivo and in vitro (Kedzierska and Crowe, 2001). Higher interleukin (IL)-6 and IL-8 levels are observed in HIV-1-infected humans and correlate with accelerated progression to AIDS (Breen et al, 1990; Matsumoto et al, 1993). IL-6 and IL-8 can signal through the Janus kinase (JAK)/signal transducers and activators of transcription (STAT) pathway, and exposure of human brain microvascular endothelial cells (HBMEC) to HIV-1 virions induce upregulation and activation of IL-6, IL-8, and STAT1 genes (Chaudhuri et al, 2008a; Chaudhuri et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…We could not find association of variants of IL-8 with risk of HIV-1 seroconversion or disease progression (A.V., M.L., and F.M., unpublished work). However, dysregulation and elevated IL-8 production (15,16) and reduced expression of IL-8 receptors, CXCR1 and CXCR2, were reported in HIV-1-infected patients (17). HIV-1 replication was shown to be up-regulated by IL-8 in macrophages and T lymphocytes, and inhibited by IL-8 antagonists and GRO-␣ (18).…”
mentioning
confidence: 99%